Factors influencing impulse buying behavior towards self care products / Nur Atiqah Mohd Rafie - Mohd Rafie, Nur Atiqah (Faculty of Business and Management, 2019)
Consumers buy products not only because of need to them but also because of sudden urge to buy them. The impulse buying behavior towards self-care products have been studied by researchers and marketing academician more than a half century. The aim of this research is to study the influence of factors such as credit card, store environment, window displays and level of income on impulse buying behavior towards self-care products. The detailed literature review of the dependent variable and independent variables were gathered and constructed appropriately in this paper. This study will be useful for researchers and practitioners towards comprehensive insight of the shopper’s impulsiveness in theoretical framework. A survey was conducted at KLCC shopping mall. The respondents were shoppers that buy self-care products at selected health & beauty stores in KLCC shopping mall. This topic is quantitative because there is certain population. Questionnaires were distributed to get their respective opinions pertaining to our topic. The findings were analyzed to answer research questions and recommendations were proposed in this paper.